1998
DOI: 10.1292/jvms.60.549
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Growth Factor Ligand and Their Receptor mRNAs in Bovine Ova during In Vitro Maturation and after Fertilization In Vitro.

Abstract: ABSTRACT. We analyzed the expression of mRNAs for growth factor [epidermal growth factor (EGF), insulin-like growth factor-I (IGF-I), basic fibroblast growth factor (bFGF) and platelet-derived growth factor A chain (PDGF-A)] and their receptor (R) by reverse transcriptionpolymerase chain reaction in bovine ova during oocyte maturation in vitro (0-21 hr) and after fertilization in vitro (6-144 hr: zygotes to blastocysts). Transcripts for EGF were not found before fertilization. Transcripts for IGF-I were presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 32 publications
6
40
1
5
Order By: Relevance
“…Gene expression of the IGF1 ligand has been detected from the zygote to the blastocyst stage in mouse embryos (Stojanov & O'Neill 2001) and immunolocalisation studies confirmed its presence, revealing a higher expression in the ICM than in the TE cells (Stojanov & O'Neill 2001). In contrast, early studies had reported the presence of mRNA for IGF1 ligand in preimplantation bovine embryos (Watson et al 1992, Yoshida et al 1998, Lonergan et al 2000, but subsequent experiments did not confirm these observations (Yaseen et al 2001, Bertolini et al 2002, Ponsuksili et al 2002, Moore et al 2007, Warzych et al 2007, Wang et al 2009). This indicates an active autocrine IGF1 circuit in mice compared with cattle, similar to that of the ovary .…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression of the IGF1 ligand has been detected from the zygote to the blastocyst stage in mouse embryos (Stojanov & O'Neill 2001) and immunolocalisation studies confirmed its presence, revealing a higher expression in the ICM than in the TE cells (Stojanov & O'Neill 2001). In contrast, early studies had reported the presence of mRNA for IGF1 ligand in preimplantation bovine embryos (Watson et al 1992, Yoshida et al 1998, Lonergan et al 2000, but subsequent experiments did not confirm these observations (Yaseen et al 2001, Bertolini et al 2002, Ponsuksili et al 2002, Moore et al 2007, Warzych et al 2007, Wang et al 2009). This indicates an active autocrine IGF1 circuit in mice compared with cattle, similar to that of the ovary .…”
Section: Discussionmentioning
confidence: 99%
“…The use of different culture media had no effect on blastocyst formation. Expression of Igf-2r is detectable at all stages of embryonic development in bovine embryos (Watson et al 1992, Yoshida et al 1998, Yaseen et al 2001. It has been postulated that insulin-like growth factors play a role as a survival factor in preimplantation bovine embryos (Yaseen et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The IGF1 receptor has been localized in bovine oocytes, cumulus cells and in both granulosa and theca cells (Yoshida et al 1998, Perks et al 1999, Armstrong et al 2001, Schams et al 2002, Nuttinck et al 2004, Sudo et al 2007. In vitro studies have shown that IGF1 synergizes with FSH to regulate the aromatase activity of granulosa cells (Spicer et al 2002).…”
Section: Introductionmentioning
confidence: 99%